AL-WAQF AL-MUNTIJ WA AL-ILTIQĀ' BAYNA AL-ISLĀM AL-TAQLĪDI WA AL-ISLAM 'ABRA AL-WAṬANI FĪ LOMBOK INDONESIA (JOURNAL OF INDONESIAN ISLAM, 2023)
This article discusses the responses and thoughts of Tuan Guru or the traditionalist ulama in Lombok on the waqf innovation proposed by ACT (Aksi Cepat Tanggap), which is an Islamic international social and philantropic organization that operates in Lombok. The main motives of the various responses is the emergence of alternative narration and thought in Lombok that relates to the new categorization of waqf which is not existent in the islamic traditional jurisprudence. Some ulama who still stick with the opinion of Shafii school of law who do not recognize the productive waqf turn to welcome to this innovation because the proposal of ACT is based on charity and welfare of Muslims. There are three arguments proposed by traditional ulama in Lombok behind their acceptance of productive waqf, namely the argument of flexibility which prioritizes the preservation of traditional jurisprudene. Still, this does not erase all reservation of this innovation. the second is social arguments which emphasizes the role of waqf in improving the quality of Muslims life in Lombok. the third is the practical  argument, in which the ACT program was not financially burdersome for the intstituion owned and run by the tuan guru of Lombok. This positive reception turns out to be the opinions of transnational Muslims in Lombok who in many instances oppose the thoughts and opinions of traditional Muslims as innovation, heresy and even infidelity. Thus, this productive waqf has become a meeting point of the two opposing groups amidst the numerous conflicting views.